(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Financial planning and budgeting form a significant part of financial management in both the individual and corporate decades. In this regard, processes such as determining financial management goals, developing a strategy for achieving goals and control and analytical control over results arise. Within the basic aspects of financial planning and budgeting cannot be achieved without ensuring financial stability, optimizing costs and using resources to achieve set goals. The paper discusses the essence of financial planning, budgeting, their main tasks, varieties.